2014
DOI: 10.2304/pfie.2014.12.5.670
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous and Immigrant Students in Transition to Higher Education and Perceptions of Parental Influence: A Bourdieusian Perspective

Abstract: This article aims to compare and contrast the perceptions of parental influence of indigenous middle-class students and immigrant students in Cyprus, and to investigate how their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The French sociologist Duru-Bellat finds that students from working-class backgrounds tend to choose vocational pathways instead of universities mainly because academic pathways are seen to be at odds with their cultural identity (2010). Similar results are confirmed in the research on the educational choices made by children of immigrant origin (Kleanthous 2014;Boado 2011). Kleanthous's study shows that students from immigrant origins are much less likely to make ambitious choices than their non-immigrant counterparts, partly because of a lack of identity fit in universities in Cyprus (2014).…”
Section: Theoretical Frameworksupporting
confidence: 83%
See 2 more Smart Citations
“…The French sociologist Duru-Bellat finds that students from working-class backgrounds tend to choose vocational pathways instead of universities mainly because academic pathways are seen to be at odds with their cultural identity (2010). Similar results are confirmed in the research on the educational choices made by children of immigrant origin (Kleanthous 2014;Boado 2011). Kleanthous's study shows that students from immigrant origins are much less likely to make ambitious choices than their non-immigrant counterparts, partly because of a lack of identity fit in universities in Cyprus (2014).…”
Section: Theoretical Frameworksupporting
confidence: 83%
“…Prior literature on Boudon's theory follows the thesis of the rational choice perspective, which examines the direct impact of individual families' socioeconomic backgrounds and financial and cultural resources on students' choices in higher education (Reay et al 2009;Kleanthous 2014;Brooks 2008). It has been shown that students from professional families tend to choose academic pathways and go to elite universities, while their working-class counterparts, even those of the same ability, are more likely to select vocational courses or less prestigious institutions (Duru-Bellat et al 2008;Thomsen et al 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourdieu refers to this mismatch between habitus and field as the hysteresis effect (Bourdieu, 1977). This idea has been used widely in research related to the experience of immigrant groups in their host countries (Kleanthous, 2014). For example, Dryden-Petersen and Giles (2010) apply the concept to understand the difficulties students with refugee backgrounds experience in accessing education.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Liu, 2019; Sovansophal, 2020; Yang & Chen, 2021). The EMI theory is helpful in explaining the influence of family background on professional choices in the existing literature (Kleanthous, 2014). It suggests that in the context of expanding higher education, family background not only affects educational opportunities, but also influences students’ educational decisions.…”
Section: Introductionmentioning
confidence: 99%